The legend and truth about the steppe queens - Aituganova, С.Ш.; Dauletova, А.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2019)
The article concludes about the heroic legends of the ancient Saka period, about the exploits of Queen Tomiris and Saks who lived in the great steppe. In the works of the great thinker Herodotus «History» he tells about the exploits of the he generals. Based on the image and traditions of the Saks, worldview, courage, shown in the name of his country, they defended the great Steppe from the enemy. It is they analyzed that the main core of the legend is the feat of Queen Tomiris, which is forever preserved in the memory of the people.Queen Tomiris is not only a legend, but also the protagonist of events created on the basis of historical truth. This work in the form of a historical legend provides specific information about the life of generals. The battle, which took place in 530-529 years BC –is not an ordinary war, but the truth of history, which defended the Homeland from dense troops under the leadership of the Persian king Saks-massagetov inhabiting the great steppe.All these circumstances are described in the legend in detail: how the war began and how it ended.In this regard, it should be noted that this legend is a historical reality based on the truth